Young men's endorsement and pursuit of appearance ideals: The prospective role of appearance investment. (March 2016) - Kling, Johanna; Rodgers, Rachel F.; Frisén, Ann
Highlights: Appearance investment prospectively predicted leanness orientation. Appearance investment predicted ideal internalization and muscularity behaviors. It might be useful to include appearance investment in sociocultural models. Prevention programs should consider targeting appearance investment. Abstract: Appearance investment has been proposed as a risk factor for the development of body dissatisfaction. Despite this, few studies have explored men's investment in their appearance. The aim of the present study was therefore to examine appearance investment as a prospective predictor of young men's endorsement and pursuit of appearance ideals. A community sample of 187 young men participated in a study at ages 21 and 24. Hierarchical multiple regressions revealed that appearance investment, as hypothesized, was a prospective predictor of increases in leanness orientation, media-ideal internalization, and muscularity behaviors. However, appearance investment did not predict increases in muscularity dissatisfaction. The present findings highlight the importance of including appearance investment in sociocultural models of the development of men's body image, and suggest that appearance investment may be an important target variable to consider when designing body dissatisfaction prevention and intervention programs tailored to young men.